2013
DOI: 10.1037/a0031888
|View full text |Cite
|
Sign up to set email alerts
|

An effect of age on implicit memory that is not due to explicit contamination: Implications for single and multiple-systems theories.

Abstract: An open access repository of Middlesex University research http://eprints.mdx.ac.uk Ward, Emma V. and Berry, Christopher J. and Shanks, David R. (2013) An effect of age on implicit memory that is not due to explicit contamination: implications for single and multiple-systems theories.Psychology and Aging, 28 (2 Copyright and moral rights to this thesis/research project are retained by the author and/or other copyright owners. The work is supplied on the understanding that any use for commercial gain is stric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 57 publications
3
55
1
Order By: Relevance
“…For instance, Buchner and Wippich (2000) reported values between and 0.41 and 0.88 for explicit recognition and recall tests in memory experiments. The figures they obtained for priming tests were even lower: 0.13–0.44 (see also LeBel & Paunonen, 2011; Ward, Berry, & Shanks, 2013). …”
Section: Testing a Key Prediction Of The Regression Accountmentioning
confidence: 96%
“…For instance, Buchner and Wippich (2000) reported values between and 0.41 and 0.88 for explicit recognition and recall tests in memory experiments. The figures they obtained for priming tests were even lower: 0.13–0.44 (see also LeBel & Paunonen, 2011; Ward, Berry, & Shanks, 2013). …”
Section: Testing a Key Prediction Of The Regression Accountmentioning
confidence: 96%
“…It is widely believed that implicit memory is preserved in normal aging, in contrast to reduced explicit memory (reviewed in Fleischman, 2007; but see Ward, Berry, & Shanks, 2013a, 2013bWard, de Mornay Davies, & Politimou, 2015). It has been suggested that the beneficial use of context information in item recognition involves implicit processes, whereas recall/recognition of target-context associations involves explicit processes.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that associations between targets and contexts are implicitly encoded by older individuals. It is widely believed that implicit (unconscious/automatic) memory processes are preserved with age, in contrast to a decline in explicit (conscious/effortful) memory processes (reviewed in Fleischman, 2007;Fleischman & Gabrieli, 1998;Mitchell, 1989;Ward, Berry, & Shanks, 2013b). Thus, while explicit recall or recognition of target-context pairs may require the type of elaborate and effortful memorial processing that is impaired with age, the beneficial use of contextual information in item recognition may call upon implicit processes that remain intact.…”
Section: A Benefit Of Context Reinstatement To Recognition Memory In mentioning
confidence: 99%
“…There are cases in the literature in which priming in older adults is significantly reduced in comparison to that in young adults (e.g., Chiarello and Hoyer, 1988; Abbenhuis et al, 1990; Davis et al, 1990; Hultsch et al, 1991; Ward et al, 2013). Moreover, in published studies that claim to have revealed preserved priming in older individuals, performance has most often been numerically reduced in these individuals compared to the young (see Fleischman and Gabrieli, 1998).…”
Section: Implicit Memory: Spared or Impaired In Normal Aging?mentioning
confidence: 99%